Student Politics and Its Impacts on Political Culture in Bangladesh A Study of Recent Trends - Joy Mukherjee (UIN Sunan Gunung Djati Bandung, 2024)
Student politics has long been an integral part of Bangladesh’s political landscape, profoundly shaping the nation’s political culture. This paper investigates the role of student politics in shaping the political culture of Bangladesh, focusing on recent trends. Historically, student movements have been powerful catalysts for socio-political change, from the Language Movement of 1952 to the Liberation War of 1971. However, the contemporary landscape of student politics has shifted towards partisanship and career-driven motives, often fostering campus violence and undermining democratic values. Using a qualitative methodology, including a review of literature and data analysis from secondary sources, this study aims to analyze the interplay between student politics and political culture. The findings reveal student politics' constructive and destructive impacts on Bangladesh’s socio-political framework. The study concludes with recommendations for reform to realign student politics with its democratic potential.